THERAPEUTIC EFFECTIVENESS OF REMAVIR AT PATIENTS WITH INFLUENZA A - Volobuyeva, O. V.; Liadova, T. I.; Sevastyanova, T. V.; Sobko, S. O. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In the article the data about clinical effectiveness of the antiviral preparation Remavir at patients with influenza A virus are presented. The etiologic structure, age characteristic, clinical displays, therapeutic effectiveness of Remavir, observable by-effects, and complications and disease outcomes is studied. It is established, that the application of the Remavir leads to authentic shortening of duration of signs of an intoxication, defeat of overhead respiratory tracts, decrease of frequency of development of complications of influenza A. Inclusion of Remavir in the scheme of complex therapy of patients with a influenza is characterized good bearable and absence of by-effects.